An experimental approach to iconicity in Dutch strong and weak verb morphology. (May 2021) - De Smet, Isabeau; Rosseel, Laura
Abstract: In Dutch, some verbs can vary in their preterite and past participle form. These verbs can either take the strong inflection (using ablaut, e.g. schuilen-school-gescholen 'hide-hid-hidden') or the weak inflection (adding a dental suffix, e.g. schuilen-schuilde-geschuild 'hide-hid-hidden'). In a diachronic corpus study, De Smet and Van de Velde (2020) show that this variation can be exapted to express aspect in an iconic manner. Their results indicate that weak preterites are used more often in durative contexts, while the shorter strong variants are used more often in punctual contexts. For the past participles, this pattern is reversed: the longer strong variants are used more often in durative contexts, while the shorter weak variants are used more often in punctual contexts. In this paper, we seek experimental validation of these results. Furthermore, we also distinguish between preterite singulars and preterite plurals, as we expect the iconicity effect to be less obvious for the latter, given that the difference in length between the strong and weak preterite plural is negligible (e.g. schuilden vs. scholen ). Participants were presented with a forced choice task where they had to choose between weak or strong preterites and past participles of nonce verbs in sentences suggesting either a durative or a punctual context. Though no general effect of aspect on verb inflection was found, results indicate a trend for a particular group of verbs that supports the corpus results from De Smet and Van de Velde (2020). Furthermore, the durative-punctual distinction was also found to be portrayed in yet another iconic manner: verb forms with vowels that are sound symbolically associated with slow long movements were used more often in durative contexts, while verb forms with vowels that are associated with quick, short movements were used more often in punctual contexts. Highlights: No general iconic effect of aspect in Dutch verb morphology is found in this study. Small iconic effect is found for verbs showing a lot of variation. Vowels associated with abrupt movements are used more often in punctual contexts. Vowels associated with slow long movements are used more often in durative contexts.